Evaluation of the Training Program on Participatory Rural Appraisal Methods Targeting Undergraduate Medical Students from the First Professional Phase - Saurabh RamBihariLal Shrivastava; Gandes Retno Rahayu; Titi Savitri Prihatiningsih (Wolters Kluwer Medknow Publications, 2024)
Background: Participatory rural appraisal (PRA) methods have been acknowledged as important tools to involve members of the community in the process of identification of their problems, the factors contributing to the development of these problems, and ways by which these problems can be resolved. Materials and Methods: A quasi-experimental study will be conducted in two stages among first professional phase medical students. In the first stage, these students will be trained on PRA methods by the trained teachers, while in the second stage, these students will implement PRA methods in the local community. The entire training process and its different components will be evaluated using validated study tools (semi-structured questionnaire), which will be administered using Google Forms. The statistical analysis will be performed using frequency and percentages, and a paired t-test will be used to compare the change in knowledge before and after training. Conclusion: In conclusion, first professional phase medical students must be trained in PRA methods and subsequently supervised to monitor their change in behavior. However, as the success of the entire program will depend on the quality of training imparted to medical students, the training program must be evaluated from the perspective of students, community, and teachers.